THE IMPACT OF SOCIAL MEDIA ON STUDENT ACADEMIC PERFORMANCE OF INTERNATIONAL BUSINESS ADMINISTRATION PROGRAM IN SAM RATULANGI UNIVERSITY MANADO - Kamuh, Dea (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Nowadays is the era of globalization and rapid development of science and technology are increasingly sophisticated. Internet is one of the results of sophistication and advancement of science and technology men-made. Social media is one of the functions of the internet. Many of problems caused social media in real life, especially real impact on the world of education. This research is designed to analyze the three proponents including social influence, time spending and social lifestyle on student academic performance of international business administration program in Manado. This research is a quantitative research that associative with multiple linear regression analysis technique. The population in this study is student of IBA, with sample of 100 respondents using simple random sampling. The result of this research shows that there is significant simultaneous and partial influence of social influence, time spending and social lifestyle on student academic performance of IBA Program in Sam Ratulangi University Manado. Therefore, to enhance the development of Student Academic Performance of IBA Program the students should create a balance between using the social media and academic activities. Â  Keywords: time, social lifestyle, academic performance